COMPARATIVE STUDIES BETWEEN CLASSICAL AND MODERN SAMPLING TECHNIQUES TO IDENTIFY THE CONTAMINANTS FROM ENTOMOLOGY ITEMS - SIMEDRU, Dorina; NAGHIU, Anca; ROMAN, Marius; MICLEAN, Mirela; BORGOVAN, Ana (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Preservation of old entomology items, although very important, is very difficult due to the contamination which they were subjected to. In order to test the items contamination level with the classical sampling method, one must be very careful because they are very easily broken and can develop mold spores due to moistening. The subject of this study is to recreate in the laboratory the stages of preserving the entomology samples by using petroleum products and naphthalene. Then the samples are subjected to two types of sampling, the classical sampling and a new sampling using a special pump for air sampling. After a month in which the items were kept in a controlled environment, the sampling procedure was performed and the sample were analyzed. The results showed differences in the results obtained by two sampling techniques. The classical method proved to be more efficient but the items which were studied presented several defects.